Astigmata and Prostigmata Acari of Medical Importance in Peru - Guillén, Zoila (1997)
This article present species of Astigmata and Prostigmata acari that produce human pathology in Peru. Patients who were seen at Instituto de Medicina Tropical Daniel A. Carrion, Huinco, and domestic dust of Lima, Lambayeque, Trujillo and Ucayali, were evaluated, as well as related articles published up to now. In this work, we found the follow Astigmata: Tyrophagus putrescentiae, Acarus siro, Suidasia sp., Dermatophagoides pteromyssinus, Glycyphagus domesticus and Sarcoptes scabiei, and Prostigmata: Demodex brevis, Demodex folliculorum, Tarsonemus sp., and Trombicula irritans.